The Use of Social Media and Internet Communication Tools in Academic Purposes of the Engineering Students at Aligarh Muslim University (AMU) - Munshi, Shamim Aktar (Journal of Information and Knowledge, 2015)
In 21st Century a lot of changes have happened, especially in the fields of education, business, industry, information communication technology etc. As a result of these phenomena, our everyday life has been changed radically. The great contribution of ICT is Internetsocial media and communication tools, which changes the educational system as well as communication system across the world. The purpose of this study is to peer how the engineering students of Aligarh Muslim University are using modern communication tools and social media in their academic purposes. The present study selected survey method and questionnaire tools to collect the sample. The study finds out that majority of the students are aware of these modern communication tools and social media. This study shows that the students are highly independent on Internet communication tools and social media for their academic and communication purposes in social life. Notably there are few problems faced by students e.g. poor connectivity, lack of infrastructure, lack of time etc.